ANALISIS MITIGASI RESIKO OPERASIONAL BISNIS PADA PT XYZ BATAM - Sry Elni Wira Yanti Gulo; Sumantika, Arsyad (LPPM Universitas Putera Batam, 2025)
PT XYZ, as a logistics service provider, faces complex operational risks such as incorrect data input in the system, limited supply availability, and sudden customer demand. These risks lead to delivery delays, inaccurate information flow, and decreased operational efficiency. This study aims to identify and analyze operational risks and develop appropriate mitigation strategies. The methods used include the Supply Chain Operations Reference (SCOR) model to map the supply chain processes (plan, source, make, deliver, and return), and the House of Risk (HOR) Phase 1 and 2 to identify the relationship between risk events and risk agents, determine risk priorities based on the Aggregate Risk Potential (ARP), and formulate mitigation strategies using the Effectiveness to Difficulty Ratio (ETD). The results show that there are 16 risk events and 17 risk agents, with 3 risk agents identified as top priorities. A total of 11 mitigation strategies were proposed, including the implementation of an ERP system, integration of an Early Warning System, and strengthening of human resource competencies. These strategies are expected to reduce recurring risks and support the sustainable improvement of PT XYZ’s operational performance.